Optimasi suhu amplifikasi DNA pada quantitative polymerase chain reaction untuk identifikasi Mycobcterium tuberculosis resistan isoniazid - Endarwati, Dwi Veni; Indra, Asep Iin Nur; Hardiana, Acep Tantan; Abror, Yogi Khoirul; Nurhayati, Betty; Merdekawati, Fusvita (Current Biomedicine, 2024)
Background: Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis and is a serious threat to global health. The methods can be used to detect and identify the bacteria is quantitative polymerase chain reaction (qPCR). In this method, denaturation and extension temperatures are determining factors of success that needs to be optimized. Objective: This study aims to optimize denaturation and extension temperatures in M. tuberculosis DNA amplification. Methods: The research used quasi-experimental design. The denaturation temperature optimized were 93, 94, 95, 96, and 97°C, and the extension temperature optimized were 58, 59, 60, 61, and 62°C. The test sample was a 1 ml sputum sample isolated from a patient with isoniazid-resistant M. tuberculosis. Optimization was performed using seven test primers, namely S315T, S315N, S315I, S315R, S315G, S315L, and R463B with the katG gene target and data analysis using Ms Excel. Data optimization results were processed with Excel by taking the lowest Ct value. Results: The results showed that the optimization temperatures for denaturation were different for each primer used. Primers S315T, S315R, and S315G, optimal with denaturation temperature of 96°C, primer S315N optimal with 94°C, primers S315I and R463B optimal with 93°C, and for primer S315L optimal with 95°C, with the most widely used temperature is 96°C. The optimal extension temperature was 58°C for primers S315T, S315N, S315I, and R463B, at 60°C for primers S315R and S315G, and at 61°C for primer S315L. Conclusion: The optimal denaturation temperature in this study was 96°C and the optimal extension temperature was 58°C.